Reducing Rat Lungworm Disease in Hawai'i Through a Collaborative Partnership With K-12 School Garden and Agriculture Projects - Howe, Kathleen; Bach, Jenny; DeCoito, Myles; Frias, Shari; Hatch, Rebecca; Jarvi, Susan (Frontiers in Public Health, 2018)
A recent increase in serious cases of rat lungworm disease impacts Hawai'i's agriculture and human health. Slugs and snails, agricultural pests, are intermediate hosts of Angiostrongylus cantonensis the rat lungworm. Infection by this parasitic nematode is the leading cause of eosinophilic meningitis globally. Infection can result from ingestion of infected produce and has caused chronic neurological problems, disability, coma, and death. There are over 200 K-12 school and youth garden, and agriculture projects throughout the Hawaiian Islands. This existing network provides an avenue for teacher and student involvement in community health education and host control programs. We collaborated with five Hawai'i Island schools connected with the Hawai'i Island School Garden Network to develop an integrated pest management plan for the control of invasive, intermediate hosts of A. cantonensis. Curricula relating to rat lungworm for grades 5–8 that support student academic achievement with a focus on science, technology, engineering, art, and math were developed. The management plan trialed the use of five different materials for shelters, which provided refuge for and easy removal of unwanted slugs and snails. Over 4,000 invasive slugs and snails were removed. Students learned how to safely dispatch pests and they collected data on species found, numbers of species removed, and shelter-type capture rates. Using the arts, students shared information at school and within their family and community. A written management plan, eleven lesson plans, and auxiliary materials are now available online. A concerted effort is needed to reduce parasite hosts if we are to reduce human cases of disease and restore public faith in local agriculture. Use of the established school garden network is an ideal avenue through which to educate the public and develop solutions for this public health problem.